Internet addiction among Turkish young consumers - (:unkn) unknown (My University, 2009)
Purpose The purpose of the paper is to profile young Turkish consumers by segmenting them over internet addiction. Design/methodology/approach To profile the segments, the study analyses the internet addiction and its preceding factors among 313 Turkish high school internet user students, aged 15-18 years old, selected on a convenience basis. The data of this descriptive study were collected by a structured questionnaire. The relationship among internet addiction and the preceding factors; demographics, internet use hours, purpose of internet use, other media consumption, gratification of internet use are examined. Findings TV consumption, internet use hours, three purposes of internet use factors as “social navigation”, “targeted navigation”, “download”, besides four gratification factors namely “diversion and means”, “improve one self”, “virtual relationship”, “virtual community” were found to explain 40 percent of variation in internet addiction. The model was tested with structural equation modeling (SEM). Then the students were clustered based on internet addiction and were profiled by the preceding factors as defined in the resulting model. Research limitations/implication The research is limited to young people in Turkey using a convenience sample with a questionnaire methodology. Future research could extend the cultural base and utilize other methods. Originality/value This is a pioneering study for internet use in Turkey. In the near future, an increase in Internet use will be expected. The paper helps Turkish marketers be aware of the Internet use experience of their young consumers. © 2009, Emerald Group Publishing Limited
Keywords: Addiction; Consumers; Internet; Turkey; Young adults